Compressibility behavior of marine clay treated by combination of coal ash and cement - Ahmad, Noor Aliza; Zainal, Intan; Md Ali, Zarina (2023)
In the geotechnical field, any soft ground area that has construction on it will face a major challenge. A lot of engineering problems could arise either during or after the construction phase due to low shear strength and high compressibility of this soil in the form of excessive settlement, slope instability or bearing capacity failure. The real challenge with marine clay is stability and settlement when construction takes place. To solve this problem, study of compressibility of stabilized marine clay will be performed. The soil stabilization study aims at improving the compressibility of marine clay by adding of coal ash and cement as the stabilizer. The aim of this study is to verify the physical properties of soft marine clay soil. Then, to determine the effect of compressibility of untreated and treated soft marine clay soil with addition of coal ash and cement (OPC) at different curing periods. The samples are classified as clayey silt with slightly plasticity since the value of plastic index (PI) is less than 7. The result of the maximum dry density is 1580 kg/m3 while for the optimum moisture content (OMC) is 20%. The void ratio of the sample decreases as the curing periods increases and the optimum ratio of fly ash to bottom ash is 50:50. Compression index and swelling index value signifies the compressibility of a soil and the value of compression index and swelling index decreases as the curing period increases. Thus, through this research the compressibility of marine clay can be improved to support load and decrease the problem of settlement on construction of soft soil